1998
DOI: 10.1136/pgmj.74.873.416
|View full text |Cite
|
Sign up to set email alerts
|

Pyrexia, anaemia and acute renal failure secondary to omeprazole

Abstract: SummaryWe present the case of a 77-year-old woman who initially presented with pyrexia of unknown origin, anaemia and mild renal impairment. When her omeprazole was stopped she improved rapidly. When omeprazole was re-started she developed fever and acute renal failure, which again settled quickly on discontinuation of omeprazole. This case demonstrates how drugs can cause severe multisystem disorders that may appear to be infective or inflammatory.Keywords: omeprazole; acute renal failure; anaemia; pyrexia; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Sixty cases met inclusion criteria. The nephritis diagnosis was confirmed by renal biopsy in 59 of the cases; 3, 4, 13, 17, 18, 21, 22, 24–27, 29, 30, 32, 35, 36, 45, 46, 48 one case demonstrated the effect upon re‐administering PPIs without any other factors associated 49 . Of these 60 cases, 47 were associated with omeprazole, six cases with pantoprazole, three with esomeprazole, two with lansoprazole and two with rabeprazole.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Sixty cases met inclusion criteria. The nephritis diagnosis was confirmed by renal biopsy in 59 of the cases; 3, 4, 13, 17, 18, 21, 22, 24–27, 29, 30, 32, 35, 36, 45, 46, 48 one case demonstrated the effect upon re‐administering PPIs without any other factors associated 49 . Of these 60 cases, 47 were associated with omeprazole, six cases with pantoprazole, three with esomeprazole, two with lansoprazole and two with rabeprazole.…”
Section: Resultsmentioning
confidence: 90%
“…Three patients required dialysis treatment in the initial phases, but only one ended up on permanent dialysis. There were four cases of documented decreased renal function upon re‐administration of PPIs 24, 32, 35, 48 . There were no reports of death due to acute renal failure in the sample.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hypersensitivity reactions towards PPI manifested as skin rash or as kidney injury occurring after prolonged intake of the drugs have been described [4,5,6]. There are very few reports on acute fever reactions upon administration of a PPI [7,8]. Here we report a case of acute drug-induced fever and inflammatory syndrome towards pantoprazole.…”
Section: Introductionmentioning
confidence: 88%
“…It was the first of many that raised the possibility of a causal association between PPI therapy and AKI. Following over a decade of isolated reports, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 2 case series were published in 2006 that systematically investigated the association between PPI therapy and AIN through retrospective review of biopsy reports ( Table 1 ). 36 , 37 The first, a study from Australia, found 18 cases with biopsy-proven AIN in 2 hospitals over a 10-year period.…”
Section: Data Linking Ppi Use and Akimentioning
confidence: 99%